Coating method of graphite radiating fin for display panel

By using powder coating and electrostatic spraying technology to form a coating on the surface of graphite heat sinks, it solves the problems of coating degradation and complicated mass production due to increased heat generation, and achieves graphite heat sink coating with high heat resistance and economic benefits. method.

CN119365334APending Publication Date: 2025-01-24INDONG ADVANCED MATERIALS INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380036061.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-28
Filing Date
2023-03-02
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the application of display panels, existing graphite heat sinks have deteriorated coatings and shortened life due to increased heat generation, and it is difficult to achieve a frameless structure during mass production, with complex processes and poor economic benefits.

Method used

Powder coating is used to form a coating on the surface of the graphite heat sink through electrostatic spraying, including the use of o-cresol epoxy resin with a softening point of 70 to 90°C and bisphenol A-type epoxy resin with a softening point of 110 to 120°C. An epoxy resin composed of a combination of polyester resin containing carboxyl groups at the end and layered clay minerals to improve the heat resistance and adhesion of the coating.

Benefits of technology

Improve the heat resistance of the graphite surface, suitable for display panels, extend the life of the coating, simplify the production process, reduce costs, and improve economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005099732240000131
    Figure BDA0005099732240000131
  • Figure BDA0005099732240000141
    Figure BDA0005099732240000141
  • Figure BDA0005099732240000142
    Figure BDA0005099732240000142
Patent Text Reader

Abstract

The invention discloses a coating method of a graphite radiating fin, which comprises the step of forming a coating layer on the surface of graphite by electrostatically spraying a powder coating on the surface of the graphite sheet. The powder coating comprises 80 to 90 parts by weight of an epoxy resin composed of 30 to 40 wt% of an o-cresol formaldehyde epoxy resin having a softening point of 70 to 90 DEG C and 60 to 70 wt% of a bisphenol A epoxy resin having a softening point of 110 to 120 DEG C, 10 to 30 parts by weight of a polyester resin having a carboxyl group at a terminal, 0.1 to 5 parts by weight of a curing accelerator, and 20 to 30 parts by weight of a layered clay mineral.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention discloses a coating method for a graphite heat sink for a display panel. More specifically, the coating method for the graphite heat sink improves the existing method of laminating a film on a graphite surface and uses a coating agent to form a coating in order to improve the heat dissipation performance of the display panel. Background Art

[0002] Heat sinks made of graphite materials such as expanded graphite generate dust or splash when processed into sheets or structures due to the low hardness of graphite materials and have poor mechanical properties and insulation. In order to solve this problem, a protective sheet is laminated on the surface during the preparation process of the graphite heat sink to prevent dust or splash generated on the graphite and ensure mechanical properties.

[0003] The applicant has developed a method of laminating a protective sheet on a graphite heat sink through the Republic of Korea registered patent gazette No. 10-2148670. Electronic devices that use heat sinks have recently tended to be miniaturized. In order to solve the heating problem caused by this, the current trend in product development is to install a heat sink of the same size as the installation part of the electronic device when installing the graphite heat sink. Therefore, the method of laminating the protective sheet without the frame as in the prior art is useful.

[0004] However, in order to achieve a frameless structure without a frame, the heat sink needs to be prepared through a complex process such as cutting it to a step within 1 mm inward compared to the outer dimensions of the heat sink, bonding the lower protective sheet and the upper protective sheet, and then stacking them to the periphery. Therefore, it is difficult to mass produce and there are problems in terms of economic benefits.

[0005] In addition, regarding the graphite surface coating technology, the Korean Patent Gazette No. 10-1430235 discloses a coating film forming technology composed of an insulating polydimethylsiloxane resin. This technology uses a coating liquid containing 30 to 90 parts by weight of a mixture of graphene and graphite and 2 to 10 parts by weight of a silicon dispersant relative to 1000 parts by weight of a solvent to apply the coating electrostatically. The coating method using a liquid coating agent has the problem that the liquid component penetrates into the graphite surface and is difficult to completely dry.

[0006] The applicant has disclosed a heat sink coating method in the Republic of Korea registered patent gazette No. 10-2333315, which improves the existing method of laminating a film on the graphite surface and forms a coating using a coating agent. If this coating method is applied, a coating can be formed on the graphite surface by a non-contact coating method using powder coating, thereby improving the efficiency of the coating process.

[0007] Displays that pursue high resolution, such as the recently developed QD display, are limited in reducing thickness due to heat generation. To improve this problem, it is necessary to improve the heat dissipation structure or a heat sink suitable for the heat dissipation structure. However, when the graphite heat sink with the coating formed thereon is applied to the display panel, the heat generation increases, causing the coating of the heat sink to deteriorate and shortening its life. Summary of the invention

[0008] The present invention aims to solve the problems of the prior art as described above. The purpose of the present invention is to provide an improved coating method for graphite heat sinks, which improves the heat resistance of the coating formed on the graphite surface by a non-contact coating method using powder coating to present performance suitable for display panels.

[0009] In order to solve the above-mentioned problem, the coating method of the graphite heat sink of the present invention comprises the step of electrostatically spraying a powder coating onto the surface of a graphite sheet to form a coating on the surface of the graphite, wherein the powder coating comprises 80 to 90 parts by weight of an epoxy resin composed of 30 to 40 weight % of an o-cresol epoxy resin having a softening point of 70 to 90° C. and 60 to 70 weight % of a bisphenol A type epoxy resin having a softening point of 110 to 120° C., 10 to 30 parts by weight of a polyester resin containing a carboxyl group at the end, 0.1 to 5 parts by weight of a curing accelerator, and 20 to 30 parts by weight of a layered clay mineral.

[0010] At this time, the graphite heat sink may be made of any one of natural graphite, artificial graphite, expanded graphite, graphene, kish graphite, or a combination thereof.

[0011] Furthermore, the step of forming a coating layer simultaneously coats the front side, the back side and the periphery of the graphite heat sink.

[0012] When the coating method of the graphite heat sink of the present invention is applied, a coating can be formed on the graphite surface by a non-contact coating method using powder coating.

[0013] Furthermore, the heat resistance of the coating layer formed on the surface of the graphite is improved to exhibit performance suitable for use in a display panel. DETAILED DESCRIPTION

[0014] The present invention is further described below. The interpretation of the terms or words used in this specification and claims cannot be limited to the common meaning or dictionary meaning. The inventor can appropriately define the concept of the relevant terms in order to explain his invention in the best way. Based on this principle, they should be interpreted according to the meaning and concept that conforms to the technical spirit of the present invention.

[0015] The coating method of the graphite heat sink of the present invention comprises the steps of electrostatically spraying powder coating onto the surface of the graphite sheet to form a coating on the graphite surface.

[0016] The coating method is a method disclosed in Korean Patent Gazette No. 10-2333315 developed by the applicant. The present invention improves the coating method to obtain physical properties suitable for use in displays.

[0017] Recently, 8K UHD displays using QD or OLED have been developed to achieve high resolution. In order to develop such displays with high resolution, it is necessary to solve not only the yield problem but also the heat generation problem. To this end, relevant personnel are developing a technology to form a coating on the surface of a graphite heat sink to improve the heat dissipation efficiency.

[0018] The process of coating the surface of the graphite heat sink is applicable to the following methods, namely, a method of coating the upper and lower surfaces of the graphite heat sink, drying and curing the coating to make the coated graphite heat sink, and then cutting the graphite heat sink; a method of cutting the graphite heat sink first, coating the upper surface of the cut graphite heat sink, drying and curing the coating, then coating the lower surface, drying and curing the coating, and finally coating the periphery of the graphite heat sink, drying and curing the coating, and coating the graphite heat sink by sequentially performing these processes. However, although the method of coating the upper and lower surfaces and drying and curing the coating can be coated by a continuous process while transferring the heat sink, the coating is not uniformly formed and the graphite heat sink with the required quality cannot be made. Although the thickness deviation of the coating can be reduced by coating the upper surface, the lower surface, and the periphery in the order of cutting the graphite heat sink, the process becomes complicated and the economic benefits are poor, and it is difficult to apply it to the actual preparation process.

[0019] In order to solve the above process problems, the applicant replaced the commonly used liquid coating agent with powder coating and implemented the coating process of the graphite heat sink by electrostatic spraying. The coating process has the advantage of being able to simultaneously coat the front, back and periphery of the graphite heat sink, thereby reducing the number of coating processes and correspondingly improving the process efficiency, and also solving the problem of non-uniform drying of the liquid coating agent.

[0020] Although the coating method using powder coating has these advantages, it is very difficult to coat the graphite surface with general powder coating. This is because there are no reaction areas on the graphite surface that can absorb coating ions, no gaps between graphite particles, and the material properties of graphite itself, such as surface hydrophobicity.

[0021] In particular, when applied to displays that generate significantly more heat, such as 8K UHD displays, problems occurred in which the adhesion of the heat sink or the heat dissipation efficiency decreased.

[0022] Therefore, in order to improve the powder coating disclosed in Korean Patent Publication No. 10-2333315, the applicant changed the resin, heat dissipating material, etc. constituting the powder coating so as to improve the physical properties.

[0023] The powder coating of the present invention comprises 80 to 90 parts by weight of an epoxy resin composed of 30 to 40 parts by weight of an o-cresol epoxy resin having a softening point of 70 to 90° C. and 60 to 70 parts by weight of a bisphenol A type epoxy resin having a softening point of 110 to 120° C., 10 to 30 parts by weight of a polyester resin having a carboxyl group at the end, 0.1 to 5 parts by weight of a curing accelerator, and 20 to 30 parts by weight of a layered clay mineral.

[0024] The powder coating previously developed by the applicant uses epoxy resin widely used in epoxy powder coatings, in particular, bisphenol A type epoxy resin with excellent chemical resistance, adhesion and high temperature characteristics. The epoxy resin induces local peeling of the layered clay mineral used as an inorganic filler in the powder coating. In order to prevent this problem, a neutral surfactant that does not react with the interlayer ions of the layered clay mineral is added to prevent layer peeling. Even so, if it is continuously in a heating environment, layer peeling will still occur and the heat dissipation efficiency will be reduced. In particular, the adhesion will also be reduced when it is used for applications such as high-resolution displays that are exposed to high temperature environments for a long time.

[0025] Generally speaking, the physical properties of o-cresol epoxy resin used as a semiconductor molding material for epoxy molding will change with the softening point. For example, if the softening point increases, the physical properties such as bending modulus, thermal expansion coefficient in the glass state, and thermal conductivity will not change, but the glass transition temperature will increase and the spiral flow will decrease. It is speculated that this is because the crosslinking density increases under the condition of increasing softening point, that is, under the condition of increasing molecular weight. Therefore, the use of o-cresol epoxy resin with a proper softening point can alleviate the problem of interlayer peeling caused by the insertion of alkyl chains into the layer, and can also enhance durability so that the adhesion can be maintained even when exposed to high temperature environments.

[0026] Furthermore, by mixing the bisphenol A type epoxy resin having a relatively high softening point into the o-cresol novolac epoxy resin at an appropriate ratio, the problem of reduced spiral flow can be solved, thereby ensuring uniformity and durability of the coating film based on the coating process.

[0027] Therefore, the epoxy resin in the present invention uses 30 to 40 weight % of o-cresol epoxy resin with a softening point of 70 to 90° C. and 60 to 70 weight % of bisphenol A epoxy resin with a softening point of 110 to 120° C. The softening point range and content range are optimized through experiments. If the content of the epoxy resin deviates from the range, poor coating or reduced coating durability will occur in the coating process using powder coating, and in particular, the heat dissipation performance will be significantly reduced over time.

[0028] Furthermore, preferably, the bisphenol A type epoxy resin uses an epoxy resin with an epoxy equivalent of 190 to 220 g / eq. This is because when the epoxy equivalent is too low, the preservation and impact resistance of the powder coating will be problematic, and when the epoxy equivalent is too high, problems will arise in the coating appearance or production efficiency. Furthermore, preferably, after applying the powder coating, a bisphenol A novolac epoxy resin containing a phenolic group is used to improve the impact resistance and production efficiency.

[0029] The content of the epoxy resin in the powder coating is in the range of 80 to 90 parts by weight. When the content of the epoxy resin is too little, the bonding strength with the graphite surface is reduced, and when it is too much, problems such as reduced curing speed and peripheral coverage ability occur. Compared with the powder coating of the prior art, the amount of the epoxy resin used is relatively large because even if a large amount of epoxy resin is contained, the layered clay mineral does not peel off and the bonding strength is improved.

[0030] Furthermore, the powder coating of the present invention contains a polyester resin containing a carboxyl group at the end as a curing agent. The carboxyl group at the end of the polyester resin promotes the ring-opening reaction of epoxy in the presence of an alkali catalyst and thereby promotes the curing of the epoxy resin. Preferably, the content of the polyester resin containing a carboxyl group at the end is in the range of 10 to 30 parts by weight. When the content of the curing agent is too little, uncured parts will occur, and when it is too much, the physical properties of the coating will decrease, resulting in a decrease in the physical properties of the graphite heat sink. The polyester resin containing a carboxyl group at the end can be prepared by reacting a carboxylic acid having 1 to 3 carbon atoms with a polyester resin in the presence of an alkali catalyst.

[0031] Furthermore, the powder coating contains a curing accelerator, and a compound whose terminal group contains a functional group that can promote curing is used. The curing accelerator can be selected from amines, imidazoles, benzoyl peroxide, or a mixture thereof. The imidazole curing accelerator can be exemplified by 2-methylimidazole, and the amine curing accelerator can be exemplified by amine adducts.

[0032] The content of the curing accelerator is in the range of 0.1 to 5 parts by weight. If the content of the curing accelerator is too little, the curing time will be prolonged. If the content of the curing accelerator is too much, the curing time will be shortened but problems such as deterioration of the coating appearance and increased surface unevenness will occur.

[0033] Furthermore, as mentioned above, the present invention uses layered clay mineral as the inorganic filler.

[0034] The above-mentioned layered clay mineral is also used in Korean Patent Publication No. 10-2333315. As mentioned above, the present invention uses an o-cresol novolac epoxy resin in order to suppress delamination of the layered clay mineral.

[0035] The layered clay minerals include, for example, layered silicates or clay minerals of silica-alumina components such as halloysite, kaolinite, smectite, montmorillonite, hectorite, saponite or vermiculite. The layered clay minerals have a large surface area of ​​more than 800 square meters per 1 gram, and have a structure in which dozens or even hundreds of very thin sheets with a thickness of 1 nm and a length of about 30 nm to 1,000 nm are stacked. If the layered structure is broken and each of the nanosheets is uniformly dispersed in the polymer matrix as a nanofiller, the following effects that cannot be achieved by existing polymer composite materials in which inorganic fillers are introduced into the polymer medium in a state of agglomeration of several microns or more can be achieved, that is, mechanical properties several times higher than those of polymer resins can be obtained with only a very small filler content, and various physical property changes such as heat resistance, electrical properties, and mechanical shielding can be achieved.

[0036] In particular, layered clay minerals can be treated as interlayer insert materials to adjust the interlayer distance, and their synthesis is relatively simple and suitable for use as fillers. The interlayer distance of graphite is about 0.7nm, so considering the characteristics of layered clay minerals with an interlayer distance of 0.9 to 1.0nm in a contracted state, even without adjusting the interlayer distance, when a coating is formed adjacent to graphite, excellent heat dissipation characteristics can be exhibited.

[0037] The interlayer distance of the layered clay mineral varies with the crystal structure. For example, the interlayer distance of kaolinite measured by X-ray diffraction is approximately The largest interlayer distance of smectite is about 10 to Furthermore, DTA analysis showed that the phase transition temperature was at least 600°C, and it was considered to be a material that exhibits high heat resistance.

[0038] From the results of preparing powder coatings using various layered clay minerals, it can be seen that the best effect is achieved when using halloysite. Halloysite is a layered clay mineral composed of aluminum silicate (Al2Si2O5(OH)4) with a structure similar to that of kaolinite. It has a characteristic structure in which water molecules exist between the layers. In the dehydrated state, the interlayer distance measured by X-ray diffraction is In the hydrated state, the interlayer distance becomes Due to this property, the possibility of alkyl chains being inserted into layers can be suppressed when mixing with polymers, and in particular, the compatibility with the epoxy resin of the present invention is excellent. For this reason, unlike the powder coating of the prior art, it is not necessary to separately mix a neutral surfactant in order to suppress layer peeling.

[0039] The layered clay mineral is used in an amount ranging from 20 to 30 parts by weight. Compared to the prior art, the heat dissipation effect of the powder coating can be improved due to the increased content of the layered clay mineral. If the content of the layered clay mineral is too little, sagging of the coating will occur and the concealment ability and heat dissipation performance will be reduced. If the content of the layered clay mineral is too much, the relative content of the resin will decrease and the physical properties of the coating will be reduced. Therefore, it is better to use it within the above range.

[0040] Furthermore, general additives such as anti-bubble agents, gloss regulators, and dispersants may be added as needed. When the additives are used, preferably, they are used in a range of 0.1 to 5 parts by weight. If the content of the additives is too little, there is no difference from when no additives are used and the effect cannot be exerted. If the content of the additives is too much, the effect brought by mixing the additives will not increase and it is not economical, and sometimes it will cause problems in the appearance of the coating.

[0041] Using the aforementioned powder coating, the front, back and periphery of the graphite sheet can be coated simultaneously by electrostatic spraying, which is a method of attaching powder coating to a surface using electrostatic force, thereby coating the entire surface of the target sheet simultaneously.

[0042] Specifically, the graphite sheet is cut into a desired size by a cutting process, the cut graphite sheet is placed in an electrostatic spraying device and then a powder coating is applied to the surface by a coating process, and the coated graphite sheet is heat-treated to adhere the powder coating to the surface by heat treatment and curing to form a coating on the graphite surface. The heat treatment is performed at a temperature of 50 to 250° C., preferably 50 to 150° C., for 30 seconds to 3000 minutes, preferably 5 to 20 minutes, in a state where the powder coating is applied, and a coating of 2 to 300 μm thick can be formed according to the process conditions, preferably a coating of 10 to 100 μm thick can be formed.

[0043] Furthermore, since it is necessary to obtain physical properties equivalent to those obtained when a general protective sheet is attached, the folding resistance of the prepared graphite sheet should be less than 1.5 inches, the pencil hardness should be B or higher, and the impact resistance should be 5 kg·cm or higher.

[0044] If the coating method of the present invention is applied, a coating can be formed on the surface of a graphite heat sink that is difficult to coat. Therefore, compared with the existing protective sheet lamination method, it is more economical and more efficient to perform the finishing work of the graphite heat sink.

[0045] In order to confirm whether the performance of the heat sink is improved when the coating method of the present invention is applied, a graphite sheet was prepared as follows and its physical properties were evaluated.

[0046] The graphite sheet used was a 500 to 920 μm thick graphite sheet produced by Indong Advanced Materials Co., Ltd. After the graphite sheet was fixed, electrostatic spraying was performed at an electrostatic voltage of 70 kV. At this time, the coating process was performed in a manner that the distance between the spray gun and the spray object was set to 25 cm and the flow rate in the working space was set to 0.4 m / sec.

[0047] The powder coating used to implement the coating process is prepared by mixing the components and contents shown in Table 1. In Table 1, the units are parts by weight. Comparative Example 3 is prepared according to the example of the Korean Patent Gazette No. 10-2333315.

[0048]

Table 1

[0049]

[0050]

[0051] The evaluation results of the physical properties of each graphite sheet are shown in Table 2. In Table 2, the folding resistance is measured according to KS M ISO 6860, the pencil hardness is measured according to KS M ISO 1519, and the impact resistance is measured according to KS M ISO-6272-2.

[0052]

Table 2

[0053]

[0054] The results in Table 2 show that the graphite sheets of Examples and Comparative Examples are excellent in folding resistance and impact resistance and the durability of the coating films is excellent. This result shows that the surface stability of the graphite sheets coated with the powder coating material of the present invention is improved.

[0055] Furthermore, the thermal diffusion capacity of the graphite sheet coated according to the coating method of the present invention was tested. After the graphite sheet was cut into a size of 100 mm in width and 10 mm in length, a double-sided tape was pasted on one side of the electromagnetic wave shielding layer and attached to the heating block. Thereafter, the temperature of the heating block was raised to 90±2°C.

[0056] After the temperature rises, the heating block is sealed in a box and stabilized for 10 minutes, and the temperature of the stabilized test piece is measured using an infrared camera. The highest temperature (hot spot) and the lowest temperature (cold spot) of the graphite sheet are obtained from the measured temperatures, and the temperature difference (ΔT) between the hot spot and the cold spot is evaluated by the thermal diffusion capacity. In other words, the smaller the ΔT, the better the heat dissipation performance can be evaluated.

[0057] In addition, considering the bonding operation of the graphite sheet, a plurality of through holes (4Фhole) were formed in the graphite sheet by punching, and then the peel strength of the through holes was measured by a 180° peel test (JIS C 6741 standard).

[0058] Table 3 shows the evaluation results of each graphite sheet.

[0059]

Table 3

[0060]

[0061]

[0062] From the results in Table 3, it can be seen that the graphite sheets of Examples 1 and 2 have excellent thermal diffusion capabilities and the peel strength of the through holes is relatively high, and the durability of the coating formed on the surface of the graphite sheet and the degree of improvement of the heat dissipation effect caused by the coating are excellent. In particular, compared with Comparative Example 3 using the powder coating of the prior art, its thermal diffusion capability and peel strength are higher and it is considered to have physical properties suitable for displays with greatly increased heat generation such as 8K UHD displays.

[0063] The rights of the present invention are not limited to the embodiments described above but are defined by the contents recorded in the claims. It is natural that a person with ordinary knowledge in the technical field to which the present invention belongs can make various modifications and improvements within the scope of the rights recorded in the claims.

Claims

1. A coating method for a graphite heat sink, characterized in that: The method comprises the steps of electrostatically spraying a powder coating onto the surface of a graphite sheet to form a coating on the surface of the graphite. The powder coating comprises 80 to 90 parts by weight of an epoxy resin consisting of 30 to 40 parts by weight of an o-cresol epoxy resin having a softening point of 70 to 90° C. and 60 to 70 parts by weight of a bisphenol A epoxy resin having a softening point of 110 to 120° C., 10 to 30 parts by weight of a polyester resin having a carboxyl group at the end, 0.1 to 5 parts by weight of a curing accelerator, and 20 to 30 parts by weight of a layered clay mineral.

2. The coating method of graphite heat sink according to claim 1, characterized in that: The graphite sheet is composed of natural graphite, artificial graphite, expanded graphite, graphene, kish graphite or a combination thereof.

3. The coating method of graphite heat sink according to claim 1, characterized in that: The step of forming a coating layer simultaneously coats the front side, the back side and the periphery of the graphite sheet.

Citation Information

Patent Citations

  • Heat-dissipating powder coating composition, heat-dissipating coating film, and coated article

    CN105073918A

  • Powder coating composition

    CN111566174A

  • Method of forming coating film on casting for processing

    JP1995018207A

  • Powder paint composition having a high glass transition temperature

    KR1020110113394A

  • Coating method for heat-conductive graphite sheet

    KR102333315B1